Interstitial brachytherapy for pediatric soft tissue sarcoma: Evolving practice over three decades and long‐term outcomes. Issue 9 (10th May 2018) - Laskar, Siddhartha; Pilar, Avinash; Khanna, Nehal; Puri, Ajay; Gulia, Ashish; Qureshi, Sajid; Chinnaswamy, Girish; Vora, Tushar; Ramadwar, Mukta
Abstract: Purpose: Evaluate long‐term clinical outcomes, adverse effects, and evolving practice of interstitial brachytherapy (BT) for pediatric soft tissue sarcomas (STS). Methods: From September 1984 to December 2014, 105 children (median age 10 years) were included. There were 60 males and 45 females. The majority (74%) had primary lesions. Synovial sarcoma (22%) was the most frequent histology. Treatment included wide local excision and BT with or without external beam radiotherapy (EBRT). Eighty‐five (81%) received BT alone. Results: After a median follow‐up of 65 months, local control (LC), disease‐free survival (DFS), and overall survival (OS) at 10 years were 83, 66, and 73%, respectively. On univariate analysis, LC was superior with tumors <5 cm versus >5 cm (93% vs. 75%, P  = 0.10), Grade I/II versus Grade III tumors (97% vs. 73%, P  = 0.01), nonround cell versus round cell histology (89% vs. 72%, P  = 0.03), and trunk/extremity versus head and neck/genitourinary sites (87% vs. 57%, P  = 0.0001). On multivariate analysis tumor size ( P  = 0.03) and location ( P  = 0.002) retained significance. Children receiving BT alone had comparable LC to those receiving BT and EBRT (84% vs. 80%, P  = 0.43). There was no difference in LC between LDR versus HDR BT (86% vs. 83%, P  = 0.30). Wound complications were seen in 6%. Subcutaneous fibrosis (25%), limb edema (6%), skeletal abnormalities (3%), and neuropathy (1%) were the late complications. One child (0.9%) developed a second malignancy after 7 years. Conclusion: Interstitial BT with or without EBRT results in excellent outcomes. Radical BT alone, when used judiciously, results in excellent local control and function with minimal treatment‐related morbidity.